Conserved linker regions and their regulation determine multiple chromatin-binding modes of UHRF1 - Tauber, Maria (Nucleus, 2015)
Ubiquitin-like with PHD and RING Finger domains 1 (UHRF1) is an important nuclear protein that is mutated and aberrantly expressed in many tumors. The protein integrates different chromatin modifications and is essential for their maintenance throughout the cell cycle. Separate chromatin-binding modules of UHRF1 have been studied on a functional and structural level. The unmodified N-terminus of histone H3 is recognized by a PHD domain, while a TTD domain specifically interacts with histone H3 Lysine 9 trimethylation. A SRA region binds hemimethylatd DNA. Emerging evidence indicates that the modules of UHRF1 do not act independently of each other but establish complex modes of interaction with patterns of chromatin modifications. This multivalent readout is regulated by allosteric binding of phosphatidylinositol 5-phosphate to a region outside the PHD, TTD and SRA domains as well as by phosphorylation of one of the linker regions connecting these modules. Here, we summarize the current knowledge on UHRF1 chromatin interaction and introduce a novel model of conformational transitions of the protein that are directed by the flexible and highly charged linker regions. We propose that these are essential in setting up defined structural states of the protein where different domains or combinations thereof are available for binding chromatin modifications or are prevented from doing so. Lastly, we suggest that controlled tuning of intramolecular linker interactions by ligands and posttranslational modifications establishes a rational framework for comprehending UHRF1 regulation and putatively the working mode of other chromatin factors in different physiological contexts.